Effect of Juice Turbidity and Yeast Lees Content on Brandy Base Wine and Unmatured Pot-still Brandy Quality - van Jaarsveld, F.P.; Blom, M.; Hattingh, S.; Marais, J. (South African Journal of Enology and Viticulture, 2017)
The aims of this project were to identify a suitable grape juice clarification technique for the attainment of the optimal brandy base wine turbidity, to determine the importance of chemical components (volatile components and long-chain fatty acids) in brandy base wine and unmatured pot-still brandy quality, and to study the effect of yeast lees content on quality. Although common industry practice is to use the grape cultivars Colombar(d) and Chenin blanc for the production of brandy base wine, the optimal conditions for Chenin blanc have been defined in this study. The juice clarification treatments applied included no settling, cold settling, whisk, large- and small-scale centrifugation and bentonite. Yeast strain 228 was compared with VIN13, large-scale (L) distillation was compared with small-scale (s) distillation, and the use of no enzyme was compared with the use of pectolytic enzyme. The data for four vintages were compiled and evaluated. Settling with or without pectolytic enzyme, bentonite, small-scale centrifugation and whisk treatments gave clearer Chenin blanc juice, higher concentrations of certain volatile components and long-chain fatty acids, and higher quality brandy base wine and unmatured pot-still brandy. No settling and large-scale centrifugation yielded the most turbid and lowest quality products. There is a definite relationship between treatments, turbidity, concentrations of esters, higher alcohols and acids, and overall brandy base wine and unmatured pot-still brandy quality. The use of yeast strain VIN13 (as opposed to strain 228), in conjunction with an increased yeast lees content of 1.5x that is normally found in brandy base wine, yielded the best quality unmatured pot-still brandy. Based on the results of this study, it is possible to recommend the best juice clarification method(s) for optimal turbidity as well as optimal levels of yeast lees addition, and to identify chemical compounds that positively relate to quality.